MODEL PENDUGAAN LIMBAH DALAM PENGUPASAN VENIR KAYU MERANTI DAN RAMIN - Suwidji Basuki; Rachman Effendi (Jurnal Penelitian Hasil Hutan, 1988)
The  wood  waste  in plywood  manufacturing can  be used as fuel  in the boiler so it is worth  while  to know  how  much waste  is produced.  The data  obtained  can  be used as input  to determine   the amount  of fuel   to be purchased  from  outside source.In  plywood  making most waste  is produced at peeling  process, i.e. at rotary cutter,  it could  make  up  to 80  % of the  total  waste produced.This  study showed   that  the  waste  of  individual log  is significantly affected by log diameter and  log quality,  the relationship  is given  by regression  model.